2022
DOI: 10.1038/s41418-022-01062-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and inflammation during obesity: “Know my methods, WAT(son)”

Abstract: Obesity is a state of low-grade chronic inflammation that causes multiple metabolic diseases. During obesity, signalling via cytokines of the TNF family mediate cell death and inflammation within the adipose tissue, eventually resulting in lipid spill-over, glucotoxicity and insulin resistance. These events ultimately lead to ectopic lipid deposition, glucose intolerance and other metabolic complications with life-threatening consequences. Here we review the literature on how inflammatory responses affect meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 113 publications
0
45
0
Order By: Relevance
“…It is thought that proliferation and differentiation of ASC are stimulated through paracrine feedback when hypertrophic growth has reached a defined limit of capacity. Pro-adipogenic signals released from engorged adipocytes may be triggered by mechanical strain [42], local hypoxia [43], or hypertrophy-induced cell death [44]. Recently, Li et al demonstrated that adipocytes from obese or insulin-resistant humans were prone to undergoing premature senescence [45], raising the possibility of a mechanism common to adipocytes that have either reached a critical size or the end of their lifespan.…”
Section: The Adipose Progenitor Pool Is Recruited To Expand Lipid Sto...mentioning
confidence: 99%
“…It is thought that proliferation and differentiation of ASC are stimulated through paracrine feedback when hypertrophic growth has reached a defined limit of capacity. Pro-adipogenic signals released from engorged adipocytes may be triggered by mechanical strain [42], local hypoxia [43], or hypertrophy-induced cell death [44]. Recently, Li et al demonstrated that adipocytes from obese or insulin-resistant humans were prone to undergoing premature senescence [45], raising the possibility of a mechanism common to adipocytes that have either reached a critical size or the end of their lifespan.…”
Section: The Adipose Progenitor Pool Is Recruited To Expand Lipid Sto...mentioning
confidence: 99%
“…In agreement, NPY , an inducer of obesity and fat storage was found intact, possibly contributing to the overall fat profile in Cetacea [90]. Although, fat deposition and obesity trigger adipose tissue inflammation in most mammals, Cetacea exhibit a healthy fat phenotype [83, 91]. This could be concurrent with the loss of inflammatory modulation by NPFF , NPS , or NPB / NPW [15, 92, 93].…”
Section: Discussionmentioning
confidence: 88%
“…Chronic inflammation and metabolic dysregulation are common features among patients with obesity [205]. SHIP1 was found to be upregulated in diet‐induced obese mice [206].…”
Section: Therapeutic Avenuesmentioning
confidence: 99%